Nutritive Value, Tannin Bioassay and Processing Effects of Acacia brevispica, A. mellifera and A. tortilis Pods as Potential Supplements for Growing Small East African Goats (SEAGs) in Baringo County-Kenya - Mutai, Paul Arap; Nandwa, A.; Sergon, Philomena; Oliech, G. O.; Yator, Monica; Meso, Doreen N.; Koech, Julius K. (African Journal of Education,Science and Technology (AJEST), 2022)
This study was conducted in Radat sub-location, Mogotio sub-county, Baringo county. The objective of the study was to evaluate nutritive value, tannin bio assay and processing effects of mature green Acacia species pods as potential supplements for growing goats in Baringo. Acacia pods were randomly collected, and prossed as: T1-control (untreated), T2- shade dried, T3-sun-dried, and T4-pods soaked in wood ash (alkali) mixed at 200gm per/liter of water for 48 hrs. respectively. They were oven- dried at 5000C for 24hrs, then ground to be able to pass through 1mm sieve, packed and transported for analysis. Experimental Design was Randomized complete block design (RCBD). Nutrient composition by proximate and Van-Soest procedures (AOAC-1995), tannin bioassay by (Makkar,2003) was used. Total extractable tannins (TET) were determined indirectly after being absorbed by the insoluble tannin–binding compound polyvinylpolypyrrolidone (PVP)and TET concentration by subtracting TET remaining after treatment by use of PVP. Concentrations of Total phenolics and Total Tannins were calculated as tannic acid equivalents (eq) expressed as g/kg DM. Total extractable condensed tannins was assayed by addition of butanol HCl (normal concentration) Fe3+ assay, which hydrolyses the Hydrolizable tannins. Data analysis was done using ANOVA and least significant difference (LSD). There was significant difference (p≤ 0.005) in all the parameters tested for all the 3 species of acacia except in the total condensed tannins. It was concluded that Acacia tortilis with a crude protein of 11.890(g Kg-1 DM), and having the least tannin content of 0.00020 mg/g DM after processing can be used as a non-conventional plant protein supplement for ruminants, and that alkali processing method can be used to reduce tannins.